Mobile Learning Technologies - Khalil Alsaadat (International Journal of Advances in Applied Sciences, 2018)
Technological development  have altered the way we communicate, learn, think, share, and spread information. Mobile technologies are those that make use of wireless technologies to gain some sort of data. As mobile connectedness continues to spread across the world, the value of employing mobile technologies in the arena of learning and teaching seems to be both self-evident and unavoidable The fast deployment of mobile devices and wireless networks in university campuses makes higher education a good environment  to integrate learners-centered m-learning . this paper discusses mobile learning technologies that are being used for educational purposes and the effect they have on teaching and learning methods.